LEADERSHIP EFFECT, COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE AT PUBLIC WORKS OFFICE AND SPATIAL PLANNING OF KARIMUN DISTRICT - Prayitno, Cahyo; Indrayani, Indrayani; Catrayasa, I Wayan; Gita Indrawan, Mohamad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the effect of leadership, compensation and motivation on employee performance with job satisfaction as an intervening variable. The population of this study were employees of the Public Works and Spatial Planning Office of Karimun Regency with a total sample of 80 respondents. Statistical data analysis using Structural Equation Modeling (SEM) with Smart PLS software version 3.0. The research data were collected using a questionnaire/questionnaire instrument. The results in this study found that leadership directly had a positive and significant effect on job satisfaction with a p-value of 0.022 <0.05, direct compensation had a positive and insignificant effect on job satisfaction with a p-value of 0.334> 0.05,